Dynamic Phasors Estimation Based on Taylor-Fourier Expansion and Gram Matrix Representation. (26th November 2018) - Petrović, Predrag; Damljanović, Nada
Abstract : The paper presents a new approach to estimation of the dynamic power phasors parameters. The observed system is modelled in algebra of matrices related to its Taylor-Fourier-trigonometric series representation. The proposed algorithm for determination of the unknown phasors parameters is based on the analytical expressions for elements of the Gram's matrix associated with this system. The numerical complexity and algorithm time are determined and it is shown that new strategy for calculation of Gram's matrix increases the accuracy of estimation, as well as the speed of the algorithm with respect to the classical way of introducing the Gram's matrix. Several simulation examples of power system signals with a time-varying amplitude and phase parameters are given by which the robustness and accuracy of the new algorithm are confirmed.